Traveler Preferences in the Digital Transformation Toward Smart Tourism Transportation - Xiaosheng Su; Ka Yin Chau; John W. K. Leung; Yuk Ming Tang (Journal of Advanced Transportation, 2025)
Smart tourism is gaining prominence in the tourism industry by improving efficiency and enhancing tourists’ satisfaction. It often involves the use of advanced digital technologies. Although integrating these technologies in transportation can yield significant benefits, but further exploration of tourist’s perceptions on digital transformation is necessary. In this research, a two-step cluster analysis was employed to segment travelers into different groups and to identify their preferences for the use of key digital technologies in transportation hubs. We surveyed 180 passengers to understand their preferences for transportation service digitization. The analysis revealed three segments of traveler preferences: (i) manual—travelers who prefer assistance from customer service officers, (ii) automated—travelers who prefer using technology-based self-service facilities, and (iii) mobile—travelers who prefer more personalized, fully digitized services. By understanding the diverse preferences of different traveler segments, tourism providers can tailor their digitization efforts to better meet customers’ needs.